Microbiome mismatches from microbiota transplants lead to persistent off-target metabolic and immunomodulatory effects - DeLeon, Orlando; Mocanu, Mora; Tan, Alan; Sidebottom, Ashley M.; Koval, Jason; Ceccato, Hugo D.; Kralicek, Sarah; Colgan, John J.; St. George, Marissa M.; Lake, Joash M.; Cooper, Michael; Xu, Jingwen; et al. (Cell, 2025)
Fecal microbiota transplant (FMT) is an increasingly used intervention, but its suitability to restore regional gut microbiota, particularly in the small bowel (SB), must be questioned because of its predominant anaerobic composition. In human subjects receiving FMT by upper endoscopy, duodenal engraftment of anaerobes was observed after 4 weeks. We hypothesized that peroral FMTs create host-microbe mismatches that impact SB homeostasis. To test this, antibiotic-treated specific-pathogen-free (SPF) mice were given jejunal, cecal, or fecal microbiota transplants (JMTs, CMTs, or FMTs, respectively) and studied 1 or 3 months later. JMT and FMT altered regional microbiota membership and function, energy balance, and intestinal and hepatic transcriptomes; JMT favored host metabolic pathways and FMT favored immune pathways. MTs drove regional intestinal identity (Gata4, Gata6, and Satb2) and downstream differentiation markers. RNA sequencing (RNA-seq) of metabolite-exposed human enteroids and duodenal biopsies post-FMT confirmed transcriptional changes in mice. Thus, regional microbial mismatches after FMTs can lead to unintended consequences and require rethinking of microbiome-based interventions. [Display omitted] •Microbes alter regional intestinal environments to enhance fitness and engraftment•Mismatches alter metabolic and immune states of host tissues and regional microbiomes•Engraftment of FMT (anaerobic) microbes in the small bowel is persistent•Regionally matched microbiota in the small and large bowel restore homeostasis Fecal microbiota transplants (FMTs) may not always effectively restore small bowel microbiota due to regional differences in gut environments, potentially causing unintended effects on metabolism and immune function. This research suggests that personalized, intestinal-region-specific microbiome therapies are needed to improve outcomes and avoid mismatches that could impact gut health and disease.